The Effect of Disaster Education of Increasing Earthquake Disaster Preparedness : A Narrative Review - Etika Emaliyawati; Didi Satiadi; Titin Sutini; Hasna Nurul Naafiah Jamaludin; Intan Nurul Khofifah; Laurentza Rikma Manika; Syifa Melya Fauziyah; Esrha Theresya Siagian (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Earthquake is a disaster that causes a lot of losses both physically, mentally and the highest cause of death compared to other disasters. This is because public knowledge about management and preparedness in dealing with disasters is lacking, so socialization related to education regarding disaster management due to earthquakes is crucial to be given to the community to minimize losses caused. So there is a need for a literature review related to the implementation of education in disaster management. Purpose: Conducted a narrative review to determine the effect of disaster education on increasing earthquake preparedness. Methods: The article search strategy used three databases (Google Scholar, EBSCO, Garuda) which were searched from 2014-2021 in the form of research reports and reviews that discussed the effect of disaster education on increasing earthquake preparedness. with the keywords Education, Earthquake Disaster, Preparedness, Education, Earthquake Disaster, Preparedness in a database search. Then the critical appraisal tools from JBI were carried out. There were six articles that met the inclusion and exclusion criteria set. Results: Shows that the provision of earthquake disaster preparedness education can be carried out by various methods, including the introduction of school-based disaster risk, with lectures, questions and answers, simulations, demonstrations, and audiovisual techniques.  The several journals above, it shows a significant difference in the form of an increase in results before being given the intervention and after being given the intervention. Conclusion: Based on the results of the literature review is that there is the effect of disaster preparedness training earthquake with methods of educational disaster on community preparedness. And this educational method can be applied to the community to increase preparedness for earthquake disasters.